STRATEGI PEMASARAN KERIPIK PISANG DI UD. HASIL ALAM SINGOJURUH KABUPATEN BANYUWANGI - sisi handayani; Kurniawan Muhammad Nur; Novilia Kareja (Jurnal Javanica, 2022)
This study aims to analyze the internal and external factors of banana chips in UD. Hasil Alam Singojuruh Banyuwangi Regency. The sampling technique in this study was purposive sampling. This study uses the IFAS (Internal Strategic Factor Analysis Summary) matrix, the EFAS (External Strategic Factor Analysis Summary) matrix, the IE (Internal External) matrix and the SWOT matrix. The results of this study indicate that UD. Hasil Alam have three strength factors, three weakness factors, three opportunity factors, and two threat factors. The research results show that the IFAS (Internal Strategic Factor Analysis Summary) value is 2.676 and EFAS (External Strategic Factor Summary) is 2.386. The results of the IE (Internal External) matrix show that UD. Hasil Alam is in position V, which is classified as the deepest Growth Strategy and Stability Strategy. The SWOT analysis of this study resulted in eight alternative strategies that can be recommended to increase the marketing of banana chips.